The influence of workplace spirituality, spiritual health and leadership on organizational outcomes - Chongvisal, Rattigorn (Kasetsart Journal of Social Sciences, 2017)
The main purpose of this study was to examine the structural relationships among workplace spirituality, spiritual health, leadership, work engagement, psychological well-being, learning organization, good corporate governance, and leading transformational change. The sample consisted of 150 middle level managers working in companies registered on the Stock Exchange of Thailand (SET). Data were collected using a questionnaire that included rating scales and open-ended questions. Item discrimination power, reliability, and validity were tested on each measure, revealing psychometrically sound properties. Path Analysis was used to test the proposed path model of the hypothesized relationships. The results revealed that workplace spirituality played a crucial role, having the highest effect on learning organization, good corporate governance, work engagement, leading transformational change, psychological well-being, and leadership, respectively. Spiritual health had the highest effect on leadership, psychological well-being, work engagement, leading transformational change, and good corporate governance, respectively. Leadership had the highest direct effect on psychological well-being, leading transformational change, work engagement, and good corporate governance. Furthermore, workplace spirituality, spiritual health, and leadership could account for 86, 66, 63, 58, and 55 percent of the variance of learning organization, psychological well-being, work engagement, good corporate governance, and leading transformational change, respectively. These results confirmed the importance of workplace spirituality, spiritual health, and leadership as factors that organizations should promote and develop to enhance work engagement, psychological well-being, learning organization, good corporate governance, and leading transformational change.